Electronic Ballast Design for UV Lamps Based on UV Dose, Applied to Drinking Water Purifier - Arenas, Luis De Oro [UNESP]; Azevedo e Melo, Guilherme de [UNESP]; Canesin, Carlos Alberto [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2016)
This paper presents a design methodology for an electronic ballast applied to ultraviolet radiation (UV) lamps for a drinking water purifier, providing adjustable UV dose in order to ensure the inactivation of microorganisms' reproduction, commonly found in untreated water, which can be harmful to human health. The design methodology is based on the multiple segment summation source model, used for defining the UV dose applied to penstock purifiers, considering immersed lamps on a water slide enclosure, which in combination with its hydraulic behavior, provide a good performance for the microorganisms UV absorption along the entire purifier structure ducts. Thus, the water purifier was designed using hydrostatic simulations, in order to ensure compliance with the NSF/ANSI Standard 55, for commercial and residential applications. Thereby, an electronic ballast that guarantees a controlled preheating process for the UV lamp electrodes before its ignition and sets the nominal power point on the steady state, was implemented in order to guarantee the designed UV dose. Furthermore, the ballast incorporates a power factor correction flyback input rectifier stage, in discontinuous conduction mode, with universal input voltage range (90 V-rms-240 V-rms), attending the limits imposed by IEC 61000-3-2 Standard, for class-C devices.
Keywords: Drinking water; electronic ballast design; multiple segment summation source (MSSS) model; ultraviolet (UV) dose; UV lamp; UV radiation; water purifier